2016
DOI: 10.1002/jso.24108
|View full text |Cite
|
Sign up to set email alerts
|

Margins for cervical and vulvar cancer

Abstract: Surgery is the primary treatment for vulvar cancer as well as early-stage carcinoma of the cervix. This article reviews the significance of margin status after surgery on overall survival, need for further surgical intervention, and role for possible adjuvant therapy. It summarizes the abundant literature on margin status in vulvar cancer and highlights the need for further investigation on the prognostic significance of margins in cervical cancer. In addition, it reviews other important operative consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
0
18
0
1
Order By: Relevance
“…Margin clearance of at least 5 mm from invasive tumor site has been associated with improved oncological outcomes in cervical cancer surgery (13,29). When this is not achieved, adjuvant radiotherapy has been found to improve overall survival (13,(29)(30)(31) at the cost of substantial morbidity. Radiotherapy can adversely affect quality of life and lead to vaginal stenosis, sexual dysfunction, and bowel and bladder symptoms (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Margin clearance of at least 5 mm from invasive tumor site has been associated with improved oncological outcomes in cervical cancer surgery (13,29). When this is not achieved, adjuvant radiotherapy has been found to improve overall survival (13,(29)(30)(31) at the cost of substantial morbidity. Radiotherapy can adversely affect quality of life and lead to vaginal stenosis, sexual dysfunction, and bowel and bladder symptoms (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In this study the iKnife had accuracy that was better than that reported for frozen section when compared to gold-standard histology between malignant and healthy tissue. Frozen section requires infrastructure (39) and prolongs operating time (29,39), while the iKnife can give nearly real-time (3 s) diagnosis without any tissue preparation, allowing immediate excision of further tissue if deemed necessary by the surgeon. A future surgical model may include sentinel lymph node dissection, which is currently tested in clinical trials (40), with on-the-spot iKnife diagnosis of presence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…A positive surgical margin is widely recognized as a significant risk factor for the recurrence of cervical cancer [61,62] . In the present study, the existence of cancer tissue within the area of surgical incision was confirmed in only 13 patients (12.7%), comparable to previously reported results [40,43] .…”
Section: Discussionmentioning
confidence: 99%
“…CK5 is known to have high levels of expression in squamous cell carcinomas and can be used as a marker of differentiation, with weaker to no expression in adenocarcinomas [ 22 ]. Given squamous cell carcinomas account for over 90% of all vulvar cancers and that CK5 is a structural protein of basal epithelial cells [ 23 ], the detection of CK5 by both MALDI-MSI was to be expected. A study characterizing the expression of CK5 in serous gynecological carcinomas of the ovaries, endometrium, fallopian tube, primary peritoneum, and cervix observed the highest level of CK5 expression in the cervical and ovarian serous carcinomas, with little to no reactivity in the endometrial, fallopian tube, or primary peritoneum serous carcinomas [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, tissues were sectioned 8 ÎŒm thick and mounted on the Indium-Tin-Oxide (ITO) coated glass slides (Bruker Daltonics, Bremen, Germany) by heating at 60 °C for 1 h. Tissues were deparaffinised in xylene for 5 min, following by two 2 min incubations in 100% ethanol, and two 5 min incubations in 100 mM NH 4 HCO 3 . The tissues were then subjected to heat induced citric acid antigen retrieval (CAAR) (10 mM citric acid, pH = 6) [ 26 ] followed by digestion with trypsin gold (Promega, Madison, WI, USA) using an ImagePrep station (Bruker Daltonics, Bremen, Germany) at 37 °C for 2 h. Peptide Internal calibrants (Angiotensin I, [Glu1]-Fibrinopeptide B, Dynorphin A and ACTH fragment [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]) and α-cyano-4-hydroxycinnamic acid (CHCA) matrix was overlaid onto the tissue sections using an ImagePrep station (Bruker Daltonics, Bremen, Germany) [ 27 ]. An ultrafleXtreme MALDI-TOF/TOF MS system (Bruker Daltonics, Bremen, Germany) was used for data acquisition in positive reflectron mode as monitored by flexControl (V3.0.1 Bruker Daltonics, Bremen, Germany) using following settings: 2 kHz, m / z 800–4000, with 100 ÎŒm spatial resolution.…”
Section: Methodsmentioning
confidence: 99%